Finite-time sliding mode control synthesis under explicit output constraint. (March 2016) - Song, Jun; Niu, Yugang; Zou, Yuanyuan
Abstract: This work deals with the input–output finite-time stabilization problem for a class of nonlinear systems by employing sliding mode control (SMC) approach. A suitable SMC law is designed to ensure that the state trajectories can be driven onto the specified sliding surface during the assigned finite-time interval. Moreover, some parameters-dependent sufficient conditions are derived such that the input–output finite-time stability (IO-FTS) during both reaching phase and sliding motion phase are attained. Simulation results are provided to illustrate the proposed approach.